Using a multilocus phylogeny to test morphology-based classifications of Polystichum (Dryopteridaceae), one of the largest fern genera - Le Péchon, Timothée; He, Hai; Zhang, Liang; Zhou, Xin-Mao; Gao, Xin-Fen; Zhang, Li-Bing (BMC evolutionary biology, 2016)
Background Polystichum (Dryopteridaceae) is probably the third largest fern genus in the world and contains ca. 500 species. Species of Polystichum occur on all continents except Antarctica, but its highest diversity is found in East Asia, especially Southwest China and adjacent regions. Previous studies typically had sparse taxon sampling and used limited DNA sequence data. Consequently, the majority of morphological hypotheses/classifications have never been tested using molecular data. Results In this study, DNA sequences of five plastid loci of 177 accessions representing ca. 140 species of Polystichum and 13 species of the closely related genera were used to infer a phylogeny using maximum likelihood, Bayesian inference, and maximum parsimony. Our analyses show that (1) Polystichum is monophyletic, this being supported by not only molecular data but also morphological features and distribution information; (2) Polystichum is resolved into two strongly supported monophyletic clades, corresponding to the two subgenera, P. subg. Polystichum and P. subg. Haplopolystichum ; (3) Accessions of P. subg. Polystichum are resolved into three major clades: clade K ( P. sect. Xiphophyllum ), clade L ( P. sect. Polystichum ), and the HYMASO superclade dominated by accessions of P. sect. Hypopeltis , P. sect. Macropolystichum , and P. sect. Sorolepidium , while those of P. subg. Haplopolystichum are resolved into eight major clades; and (4) The monophyly of the Afra clade (weakly supported), the Australasian clade (weakly supported), and the North American clade (strongly supported) is confirmed. Conclusions Of the 23 sections of Polystichum recognized in a recent classification of the genus, four ( P. sect. Hypopeltis , P. sect. Neopolystichum , P. sect. Sorolepidium , P. sect. Sphaenopolystichum ) are resolved as non-monophyletic, 16 are recovered as monophyletic, and three are monospecific. Of the 16 monophyletic sections, two ( P. sect. Adenolepia , P. sect. Cyrtogonellum ) are weakly supported and 14 are strongly supported as monophyletic. The relationships of 11 sections (five in P. subg. Haplopolystichum ; six in P. subg. Polystichum ) are well resolved.